Which Subgroup of First-Episode Schizophrenia Patients Can Remit During the First Year of Antipsychotic Treatment? - Cheng, Zhang; Yuan, Yanbo; Han, Xue; Yang, Lei; Zeng, Xin; Yang, Fude; Lu, Zheng; Wang, Chuanyue; Deng, Hong; Zhao, Jingping; Yu, Xin (Frontiers in Psychiatry, 2020)
Objective To investigate the persistent remission rate (PRR) and its predictors within the first year of antipsychotic treatment in first-episode schizophrenia (FES) patients. Methods In a sample of 301 FES patients who remained in antipsychotic treatment for 1 year, we assessed symptoms with the Positive and Negative Syndrome Scale (PANSS), cognition in six domains and functioning with the Personal and Social Performance Scale (PSP). Results In total, 75.4% (227/301) of FES patients remaining in antipsychotic treatment reached persistent remission (PR) in one year. The PSP score was higher in remitters than non-remitters at the endpoint of the 1-year follow-up (P <0.0001). The PANSS negative score—but not the PANSS total score, positive score or general psychopathological score; PSP score; or cognitive performance at baseline—was negatively associated with PR. Lower scores for “abstract thinking” and “stereotyped thinking” were independent predictors of PR. Conclusions In FES, nearly 3/4 patients could achieve PR with 1 year of antipsychotic treatment, and having fewer negative symptoms, especially thinking and volition symptoms, can predict PR. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT01057849.